Enrichment in Architecture An Explorative Study ofthe Formal Enrichment Achieved by Contrast - Asma Hasan alâ€ Dabbagh (Iraqi Journal of Architecture and Planning, 2009)
Architectural literatures and practices presented the concept of Enrichment asone of the solutions for the problems of Modemism. The importance of this conceptemerges due to its relation with other phenomena like visual complexity and ambiguity.Enrichment is a product character and a strategy to its creation. This productpossess abundance and detail in the visual tools causing the meaning enrichment and itsreadiness for multi interpretations.This concept is present in to two levels; the first, formal and includescomplexity and riddles, while the second is moral which includes the multiinterpretations.These sub-concepts cover many tools to achieve it like redundance,contrast, formal transformations, slight contrast within a strong order and an ambiguousmeaning.This research dealt with contrast in its practical study. It defined this tool withits major and secondary variables. Also, this study tried to explore the possiblecharacteristics and values generating contrast by applying it on two architecturalprojects. The results showed new characteristics and values for contrast which were notmentioned by previous literatures. In addition, the conclusions showed that thearchitects depend on contrast in forms reference which in tum affect the total andperipheral characteristics ofthese forms. The latter conclusion supports the contexts ofprevious literatures.